2016
DOI: 10.15253/2175-6783.2016000500014
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload in mental health

Abstract: Objective: to compare the workload in nursing mental health professionals who work in the public service and the private service. Methods: this is a quantitative research conducted with 70 nursing professionals in two services. For data collection, the evaluation scale of the work impact on mental health services was applied. Results: in the overall analysis, there was no statistically significant difference in the average score for workload among professionals of both institutions. However, all subscale avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…12 O processo de luta das mulheres proporciona uma possibilidade de estudar, de se profissionalizar e conseguir sua independência econômica; conquistada pela mulher, favoreceu o predomínio destas nos trabalhos da área da saúde. 12,13 A maioria dos profissionais da equipe possuía idade entre 39 e 59 anos, era casada, com formação de nível superior, especialização, pós-graduação e atuava no local há mais de cinco anos. Resultados semelhantes foram encontrados em outros estudos.…”
Section: Discussionunclassified
“…12 O processo de luta das mulheres proporciona uma possibilidade de estudar, de se profissionalizar e conseguir sua independência econômica; conquistada pela mulher, favoreceu o predomínio destas nos trabalhos da área da saúde. 12,13 A maioria dos profissionais da equipe possuía idade entre 39 e 59 anos, era casada, com formação de nível superior, especialização, pós-graduação e atuava no local há mais de cinco anos. Resultados semelhantes foram encontrados em outros estudos.…”
Section: Discussionunclassified
“…In Brazil, studies indicate that the dissatisfaction of health professionals is related to the accumulation of activities and the scarce prospects of obtaining new knowledge, impairing the quality of their performance with the patient [9]. These weaknesses end up negatively impacting patient safety culture [37,38]. It is of utmost importance that all professionals involved in the management and operation of the evaluated units understand that the error is a great learning opportunity and not reprisals to colleagues in the face of situations that may put the patient at risk [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…These weaknesses end up negatively impacting patient safety culture [37,38]. It is of utmost importance that all professionals involved in the management and operation of the evaluated units understand that the error is a great learning opportunity and not reprisals to colleagues in the face of situations that may put the patient at risk [37,39].…”
Section: Discussionmentioning
confidence: 99%
“…Another dimension found, the emotional, included 11 articles the focus of which was on: identifying stressors in the workplace and coping strategies (25)(26)(27)(28)(29) ; work environment and psychosocial risks: exhaustion (30) ; social support and quality of life (31) ; WL and quality of care (32) ; work overload (33) ; conflict and satisfaction (34) ; and violence at work (35) . Based on patients' level of dependence, it was found that 10 employees per day was insufficient, and 12 proved to be adequate to generate a score of "good" or "very good" in the care quality.…”
Section: Iv) Data Analysismentioning
confidence: 99%